International Outsourcing of Quality Healthcare Through Tele-Medicine: Binding Arbitration Makes Tele-Medical Dream a Reality - Meenakshi Kalra; Vikas Gupta (Institute of Medico-legal Publications Pvt Ltd, 2022)
The development of communication technologies has a dramatic influence on culture. The internet, cell phones and e-mail are different domains, and if health care professionals want to join this space, they will be careful to do so. Telemedicine has medical-legal implications for aspects of identification, licensing, insurance, protection, privacy and confidentiality, as well as other risks related to online healthcare communication. The International Advisory Group of the World Health Organization (WHO), which met in Geneva in 1997, identified telemedicine as providing healthcare services, where distance is a critical factor, to health care providers, who use the information and communications technologies to exchange relevant information for the diagnosis, treatment and prevention of diseases and injuries, and to continue to do so. In the context of the COVID-19 Pandemic Lockdown, the Indian Government has authorized telemedicine legal status. The Governing board, established by the Government at a meeting of the Indian Medical Council with the Ministry of Health and Family Welfare’s approval, published a notice dated 25 March 2020 (‘Amendment’) modifying Guidelines of the Indian Medical Council 2002 on telemedicine in India. The amendment introduced ‘Telemedicine consultation’ to the law. A basic knowledge of how medical negligence compensation is calculated and adjudicated in the judicial courts of India. The paper concludes with an assessment of the rules. This paper will seek to determine whether binding arbitration is the best possible solution to resolving malpractice disputes, or whether traditional litigation, while costly, is the safest choice. To do this, the paper will examine both the advantages and the disadvantages associated with using arbitration as opposed to litigation